2018
DOI: 10.1007/s11244-018-1121-0
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Sulfur Poisoned Pd–Pt/CeO2–ZrO2–Y2O3–La2O3 and Pd–Pt/Al2O3 Methane Oxidation Catalysts

Abstract: The poisoning of Pd-Pt/Al2O3 and Pd-Pt/CeO2-ZrO2-Y2O3-La2O3 methane oxidation catalysts by SO2 was studied under conditions typical for lean burn gas engines. Regeneration of sulfur-poisoned catalysts was achieved by applying rich conditions at 500 °C and 550 °C. The presence of NOx resulted in a slower deactivation rate. While Pd-Pt/CeO2-ZrO2-Y2O3-La2O3 showed a superior catalytic activity, durability and regeneration ability over Pd-Pt/Al2O3 under NOx-free reaction conditions, its reactivation by a rich trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…In one of our previous studies [56] we found PdS being unstable in the presence of oxygen and observed immediate transformation to PdO. Complementary activity tests after regenerating a sulfur poisoned sample of each catalyst formulation by application of a TPR up to 750°C confirm these findings.…”
Section: Catalyst Regeneration By Temperature Programmed Reduction (C...supporting
confidence: 72%
See 1 more Smart Citation
“…In one of our previous studies [56] we found PdS being unstable in the presence of oxygen and observed immediate transformation to PdO. Complementary activity tests after regenerating a sulfur poisoned sample of each catalyst formulation by application of a TPR up to 750°C confirm these findings.…”
Section: Catalyst Regeneration By Temperature Programmed Reduction (C...supporting
confidence: 72%
“…Application of a H2-containing atmosphere resulted in Pd4S-formation. Similarly, in one of our recent operando X-ray absorption spectroscopy (XAS) study we found PdS formation during dynamic lean-rich catalyst operation in presence of SO2 [56].…”
Section: Introductionsupporting
confidence: 59%
“…In the context of a CeOx/Pt(111) inverse model catalyst, Suchorski et al [62], for instance, proposed an "active border" between CeOx and Pt as reason for enhanced catalytic activity. However, previous findings indicate that these interactions, namely the high attraction between Pt and CeO2 [60], may cause a separation of the noble metals in bimetallic Pt-Pd catalysts supported on ceria-containing support materials [63]. Therefore, it will be interesting to expand the fundamental investigations discussed in our present study into bimetallic catalyst samples with alternative support materials.…”
Section: Discussionmentioning
confidence: 88%
“…The formation of sulfates on Pd at temperatures below 723 K has been recently described for core-shell Pd@CexZr1−xO2 nanoparticles deposited on alumina, with spillover of sulfur species onto the support detected only above 773 K [132]. Moreover, the easier regeneration of a Pd-Pt/CeO2-ZrO2-Y2O3-La2O3 methane oxidation catalyst compared to Pd-Pt/Al2O3 was found to be canceled when nitrogen oxides were added to the reaction, due to the presence of more stable PdO phase capable to link sulfates that could not be reduced during regeneration in rich conditions [133]. This should be kept in mind, since the presence of NOx is ubiquitous in automotive exhaust gases.…”
Section: Poisoning and Deactivation Of Pd-based Catalystsmentioning
confidence: 99%